Banking on graduates : a longitudinal study. - Chow, Han Siong. (2008)
The study was conducted to identify the bank products/services used by the well educated in three defined stages of their life cycle, and to study the effects of the perceived mean usefulness and the number of bank products/services used in relation to the satisfaction of the respondents. A survey was administered to eighty undergraduates and ninety graduates from the School of Accountancy and Business, Nanyang Technological University.